La tutela cautelar en el contencioso-administrativo de Nicaragua - Arríen Somarriba, Juan Bautista (2018)
The system of precautionary measures in both Nicaraguan constitutional and administrative justice has been based on the traditional suspension of the administrative act, without taking into account that, for example, in administrative inactivity there is no act to suspend, but it has not been regulated as part of effective judicial protection, approved in the recent constitutional reforms, proper to due process and minimum procedural guarantees. This closed system has lagged behind in relation to the open nature of numerus apertus, of unnamed measures, foreseen in Spanish, Colombian comparative law, among others, above all in the regulation of the concurrence of causes of the danger of legal harm by the delay of the final judgment (periculum in arrears) and the fumus bonis iuris or appearance of the good right. In this context, before the approval of a new Nicaraguan administrative litigation regulation, we have the opportunity to influence the development of this matter, offering lege ferenda proposals.